The legal protection of the rights to service inventions: issues of the legal regulation - Белуга, Ю. М.; Омельченко, Г. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In this article an authors analyze the issues of the regulation and legal protection of service inventions andproduce its main issues.